2020
DOI: 10.1186/s13048-020-00660-5
|View full text |Cite
|
Sign up to set email alerts
|

Activated CAMKKβ-AMPK signaling promotes autophagy in a spheroid model of ovarian tumour metastasis

Abstract: Background: A hallmark of epithelial ovarian cancer (EOC) metastasis is the process of spheroid formation, whereby tumour cells aggregate into 3D structures while in suspension in the peritoneal cavity. EOC spheroids are subjected to bioenergetic stress, thereby activating AMP-activated protein kinase (AMPK) signaling to enter a metabolically quiescent state, which can facilitate cell survival under nutrient-limiting conditions. Independently, we have also demonstrated that EOC spheroids induce autophagy, a pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…Lastly, it is important to consider that glycolysis mediated by GLUT1 expression and AMPK activation has been observed to markedly enhance OvCa tumor cell proliferation [ 91 ]. More recently, AMPK was shown to be indispensable for autophagy-mediated OvCa spheroid survival and proliferation [ 92 ], although whether and how it was influencing this phenotype has yet to be clearly defined. Although the majority of in vitro data using metformin in HGSOC and other OvCa cell lines demonstrate inhibited proliferation and colony formation [ 18 , 85 ], both of these pro-tumorigenic mechanisms could potentially be promoted by metformin through its well-defined upregulation of GLUT1 expression and AMPK activation.…”
Section: Considerations For Metformin On Immune Cell Metabolismmentioning
confidence: 99%
“…Lastly, it is important to consider that glycolysis mediated by GLUT1 expression and AMPK activation has been observed to markedly enhance OvCa tumor cell proliferation [ 91 ]. More recently, AMPK was shown to be indispensable for autophagy-mediated OvCa spheroid survival and proliferation [ 92 ], although whether and how it was influencing this phenotype has yet to be clearly defined. Although the majority of in vitro data using metformin in HGSOC and other OvCa cell lines demonstrate inhibited proliferation and colony formation [ 18 , 85 ], both of these pro-tumorigenic mechanisms could potentially be promoted by metformin through its well-defined upregulation of GLUT1 expression and AMPK activation.…”
Section: Considerations For Metformin On Immune Cell Metabolismmentioning
confidence: 99%
“…However, it is regarded as a key mechanism that can promote cancer cell survival under hypoxia in avascular tumours, nutrient depletion in rapidly growing tumours, or in the face of chemotherapy [ 30 ]. Indeed, our group observed that autophagy is rapidly induced in EOC spheroids, and this is driven by two parallel signaling pathways working in opposite orientations: downregulation of Akt-mTOR and upregulation of AMPK [ 10 , 17 ]. Interestingly, we also determined that the canonical Beclin-1 mechanism for autophagy activation is not required in EOC spheroids, however ULK1 within the autophagy initiation complex (AIC) is activated and required in EOC spheroids [ 17 , 28 , 30 ].…”
Section: Tumour Dormancy In Eocmentioning
confidence: 99%
“…A major downstream effect mediated by AMPK activity in EOC spheroids is the induction of macroautophagy. AMPK expression and activity, particularly that controlled by CAMKKβ, are required for induction of autophagy in HGSOC spheroids [58]. AMPK activity also acts to control cell proliferation by inducing cytostasis under nutrient-limiting conditions [57].…”
Section: Signaling Pathway Dependencies In Dormancymentioning
confidence: 99%
“…Autophagy is rapidly induced in HGSOC spheroids (Fig. 2A), and this is driven by two anti-parallel signaling pathways that were introduced in the signaling section above, namely the downregulation of AKT and the upregulation of AMPK [53,58]. More recently, a primary target of AMPK, the unc51-like protein kinase 1 (ULK1) within the autophagy-initiation complex (AIC), was shown to be activated and required for survival in HGSOC spheroids [65].…”
Section: Autophagy and Dormancy Specific Metabolismmentioning
confidence: 99%